Optimalisasi Kemampuan Komunikasi melalui Pelatihan Public Speaking pada Pegawai dan Anggota Dharma Wanita Persatuan (DWP) Balai Besar Karantina Hewan, Ikan, dan Tumbuhan (BBKHIT) Papua - Restu Monika Nia Betaubun; Rostini Anwar; Rudini Hasyim Rado (Jurnal Pengabdian Masyarakat, 2026)
This activity aims to optimize employee communication skills through public speaking training at the Animal, Fish, and Plant Quarantine Center (BBKHIT) Papua. This is based on the importance of effective communication skills, especially in socializing a program in the basis of public service, particularly in conveying and expressing knowledge that has been acquired verbally during interactions with the community. The methods used include interactive lectures, simulations, direct practice, and feedback-based evaluation. The training focused on improving communication skills, as well as touching on aspects of self-confidence in arguing, mastery of audiences especially during meetings, discussions, or seminars, and the use of effective verbal and non-verbal language to attract audience sympathy. Participants were employees and members of the Dharma Wanita Persatuan BBKHIT Papua who were directly involved in public service. The results of the activity showed a significant increase in the ability of participants to convey information systematically, clearly, and persuasively. In addition, there was an increase in the aspect of self-confidence in public speaking. Evaluation of the activity was carried out through pre-tests and post-tests as well as observations during the practice. The evaluation results showed that the public speaking training had a positive impact on improving the quality of employee communication with an average increase of around 15-20 points. Thus, this activity is expected to support the improvement of the quality of public services within the BBKHIT Papua environment and strengthen the institution’s image in the eyes of the public.